Activator-Mediated Pyruvate Kinase M2 Activation Contributes to Endotoxin Tolerance by Promoting Mitochondrial Biogenesis - Yi, Zhujun; Wu, Yilin; Zhang, Wenfeng; Wang, Tao; Gong, Jianping; Cheng, Yao; Miao, Chunmu (Frontiers in Immunology, 2021)
Pyruvate kinase M2 (PKM2) is a key glycolysis enzyme, and its effect on macrophages has not been entirely elucidated. Here, we identified that the PKM2 small-molecule agonist TEPP-46 mediated PKM2 activation by inducing the formation of PKM2 tetramer and promoted macrophage endotoxin tolerance. Lipopolysaccharide (LPS)-tolerant mice had higher expression of the PKM2 tetramer, which was associated with a reduced in vivo immune response to LPS. Pretreatment of macrophages with TEPP-46 resulted in tolerance to LPS stimulation, as demonstrated by a significant reduction in the production of TNF-α and IL-6. We found that TEPP-46 induced mitochondrial biogenesis in macrophages. Inhibition of mitochondrial biogenesis by mtTFA knockdown effectively inhibited TEPP-46-mediated macrophage tolerance to endotoxins. We discovered that TEPP-46 promoted the expression of PGC-1α and that PGC-1α was the key regulator of mitochondrial biogenesis in macrophages induced by TEPP-46. PGC-1α was negatively regulated by the PI3K/Akt signaling pathway. Knockdown of PKM2 or PGC-1α uniformly inhibited TEPP-46-mediated endotoxin tolerance by inhibiting mitochondrial biogenesis. In addition, TEPP-46 protected mice from lethal endotoxemia and sepsis. Collectively, these findings reveal novel mechanisms for the metabolic control of inflammation and for the induction of endotoxin tolerance by promoting mitochondrial biogenesis. Targeting PKM2 appears to be a new therapeutic option for the treatment of sepsis and other inflammatory diseases.